Словарь-справочник экономиста АПК: справочное издание / В.П. Коровкин, И.А. Ламыкин, А.Г. Зельднер - Коровкин Виктор Петрович (Экономика, 1990)
Экземпляры: К. Х. (20230314) / Инвентарный номер: 26880 / Цена: 2.40 / Сис.шифр: 65.9(2)32 / Авт.знак: К68 / ГРНТИ: 06.71.07 / ББК: 65.9(2)32 я21